Groundwater potential in mining regions for drinking water supply: A case study of the Żelatowa intake (Chrzanów, Poland) - Katarzyna Wawrzonek; Katarzyna Wątor; Mateusz Topolewski; Agata Kasprzak; Ewa Kmiecik (Water Resources and Industry)
Sustainable development of groundwater resources in regions affected by mining activity requires a comprehensive view of the problem from both a hydrogeological and hydrogeochemical perspective. As groundwater serves as a main source of drinking water in many regions of the world, it is necessary to recognise the potential of mine waters and their real influence on its quality. This study analyses the long-term dynamics of changes in drinking water quality from deep wells S1, S2, and S3 comprising the Żelatowa intake (Chrzanów, Poland), which is located in an area of intensive mining activity. Analysis of the data showed that mining operations are affecting water quality, as observed by upward trends for electrical conductivity, total hardness, and concentrations of certain ions between 2016 and 2021, and downward trends from 2022 onwards. The greatest adverse changes in water quality were observed in well S2 (Fe2+, Mn2+, SO42− concentrations and total hardness do not meet the requirements of Directive 2020/2184), the water requiring mixing with water from other wells to ensure that it is of suitable quality for drinking purposes. The PHREEQC software was successfully used to predict the chemical composition of the final mixture, which meets the requirements of appropriate regulations. The water from the Żelatowa intake can have an adverse effect on the water supply system, which has been proven by several scaling and corrosion indices. Continuous monitoring of the physicochemical parameters of these waters is essential to ensure the safety of the drinking water supply for the surrounding population.